Research Data Management Within the EU Data Policy Framework - Milčiuvienė Saulė; Amilevičius Darius; Raškinis Gailius (Baltic Journal of Law & Politics)
The rapid digitalization has significantly influenced EU research policy, particularly in open science and research data management. While free access to research data is integral to open science, the broader concept of research data management extends beyond mere accessibility. The EU has introduced various regulations to address the evolving challenges of digital technologies, balancing innovation with fundamental legal principles such as privacy and intellectual property protection. Although no single legal framework is dedicated to research data, multiple EU policies directly impact its management. The Open Data Directive emphasizes the reuse of publicly funded research data, promoting open access while safeguarding intellectual property and privacy rights. The Data Governance Act complements this by creating a framework for reusing protected public sector data, balancing openness with the need to protect commercial, intellectual, and personal data. The Data Act primarily focuses on private sector data and facilitates data sharing across businesses and sectors, particularly in the domain of the Internet of Things, while promoting interoperability and fair contractual terms. Despite these robust EU-level frameworks, Lithuania’s national policies lag behind, particularly in addressing the growing needs of artificial intelligence innovation.